The Relationship between Smoking and Hemoglobin Levels in Men Aged 30-40 Years in Nggaro Kumbe Hamlet - Islamy, Muhammad Habiel; Rizki, Mohammad; Arsatt, Maz Isa Ansyori (Jurnal Biologi Tropis, 2024)
Smoking is the act of inhaling smoke resulting from burning plants such as Nicotiana rustica , Nicotiana tabacum, and other types of plants whose smoke contains dangerous substances such as nicotine and tar which have been converted into cigars. The aim of this research is to provide understanding and awareness to the public about the impact of smoking, so that it is hoped that it can reduce the rate of cigarette use. The method used in carrying out this research is a cross-sectional method and the data obtained is primary data taken using consecutive non-random sampling techniques. The materials used were a questionnaire to measure the respondent's smoking status and an Hb meter to measure the respondent's hemoglobin levels. The data analysis process was carried out using analytical tests, namely the Chi-square test with the test value said to be relevant or significant with a p-value <0.05. After conducting analytical tests, the results showed that there was a significant relationship between smoking frequency and hemoglobin levels (p=0.00), no relevant or significant relationship was found with type of cigarette (p=0.09) and duration of smoking (p=0 .58) on hemoglobin levels. Researchers provide advice to the East Rabadompu Subdistrict to establish rules or policies that can reduce or eliminate smoking habits in the community. The entire community of East Rabadompu Subdistrict is expected to reduce or eliminate the habit of smoking considering the bad impact it can have on the wider community.